Allergen immunotherapy in children and adolescents with respiratory diseases - Tosca, Maria Angela; Licari, Amelia; Olcese, Roberta; Castagnoli, Riccardo; Marseglia, Alessia; Marseglia, Gian Luigi; Miraglia del Giudice, Michele; Martelli, Alberto; Calvani, Mauro; Caffarelli, Carlo; Duse, Marzia; Cravidi, Claudio; et al. (Acta Biomedica Atenei Parmensis, 2020)
To date, the only disease-modifying treatment strategy for allergic rhinitis and asthma is allergen immunotherapy (AIT). There is evidence that AIT improves allergic rhinitis and asthma, such as reducing symptom severity and medication use and improving of quality of life, with a long-lasting effect after the end of the course. The recent clinical trials evidenced AIT effectiveness and safety in allergic asthma. Consequently, the current version of the GINA (Global Initiative for Asthma) guidelines recommend AIT as an add-on therapy for asthma. There is also evidence that AIT may exert preventive activity on the possible progression from allergic rhinitis to asthma in children and the onset of new sensitizations.